Dynamic and spillover effects of armed conflicts on renewable energy in Subsaharan Africa - (:unkn) unknown (My University, 2025)
This paper analyzes the impact of armed conflicts on the renewable energy consumption in 46 Sub-Saharan African countries over the period 2000-2020. It uses a dynamic spatial econometric method to capture the spatial and dynamic effects of these conflicts on renewable energy consumption. Using the dynamic and spatial method of the Durbin model, the main results show that armed conflicts have a significant negative impact on renewable energy consumption. The effect is to 30.97% for the dynamic model against 31.28% for the non-dynamic model. The spatial effects of these conflicts show us that armed conflicts, through their contagion and spillover effects, have a significant and negative impact on renewable energy consumption in the region of 32.11%. The short- and long-term results are generally negative and significant. For heterogeneity, results show that the effect of terrorism is larger than the effect of other types of conflict. Moreover, the impact of armed conflict on renewable energy consumption is greater in the Sahel than in the rest of our sample. This article shows that the effect of conflict on the consumption of renewable energy passes through three main transmission channels : economic development, the increase in military spending as a result of conflict, to the detriment of green investment, and uncertainty, which penalizes investment and the production of renewable energy.
Keywords: African Research